Diagnostic Pleural Fluid Cytology of Nocardial Infection in A Patient of Systemic Lupus Erythematosus - Singh, Sneha; Gupta, Prajwala; Bhardwaj, Minakshi (Annals of Pathology and Laboratory Medicine, 2019)
Systemic lupus erythematous is a chronic autoimmune inflammatory connective tissue disease. Infection remains the major cause of morbidity and mortality in such autoimmune disorders. Nocardia is an uncommon opportunistic pathogen. Due it its low incidence it is often missed by clinicians and pathologists. Delay in diagnosis and treatment is the major cause of dissemination and complications of this disease. Here we report a case of nocardiosis diagnosed on pleural fluid cytology smears using special stains. A known case of systemic lupus erythematous diagnosed 7 years back complained of heaviness in chest, shortness of breath and fever. Ultrasonography of chest showed pleural effusion and consolidation of underlying lung. Pleural fluid was aspirated and sent for cytology. Giemsa and Papaniculaou stained smears showed dense degenerated acute and chronic inflammatory cells in a necrotic background with negatively stained shadows which were negative for ZN and PAS stains. However, gram stain and modified ZN stain (1%H2SO4) showed positively stained clumps of long branching filamentous organism; consistent with Nocardia spp which was later confirmed by culture studies. This case highlights the importance of high index of suspicion for nocardia in cytology samples of pulmonary origin, especially in cases patients with immunosuppressed states. More so special stains like Gram’s stain and modified ZN stain in such cases can aid in a definitive diagnosis.